Variables involved in the perception of psychological harassment in the nursing work environment Variables relacionadas con la percepción del asedio moral en el ambiente laboral de la enfermería Variáveis envolvidas na percepção do assédio moral no ambiente laboral da Enfermagem - Kátia Biagio Fontes; Maria Dalva de Barros Carvalho (Universidade de São Paulo, 2012)
This is a descriptive-exploratory study with a quantitative approach, with the objective of identifying how nurses perceive psychological harassment at work, the behaviors experienced and the variables involved. In collecting data, two questionnaires were used: one socio-professional and another for identifying the behaviors involving psychological harassment experienced by the subjects in the previous twelve months, along with the duration and frequency of the behaviors. At the end of the questionnaire, a dichotomous question was added, which addressed nurses' perceptions in relation to feeling victimized by psychological harassment at work. Both the questionnaires were applied in electronic and print format between May and September 2010. The data was analyzed through descriptive statistics. The results showed that some of the subjects felt that they were victims of psychological harassment. Only the variables related to characterization of the psychological harassment presented significant association. The following were highlighted among the most-referred-to behaviors: "They question your decisions" and "You receive verbal attacks criticizing work you have done". It's important to open spaces for discussing violence at work, so that managers may establish strategic measures for preventing and containing this type of violence, so as to ensure health, dignity and well-being at work. It is also important to discuss this issue in the academic space, so as to give the theme greater visibility, such that future nurses will be able to identify and appropriately confront this type of violence. Estudio descriptivo-exploratorio de abordaje cuantitativo, con el objetivo de identificar la percepción de enfermeros sobre el asedio moral en el trabajo, las conductas vividas y las variables relacionadas. En la recogida de datos se utilizó un cuestionario socio-profesiográfico y otro para identificar las conductas de asedio moral vividas por los sujetos en los últimos doce meses, el periodo y la frecuencia de las conductas. Al final del cuestionario fue adicionada una cuestión dicotómica relacionada a la percepción del enfermero cuanto a sentirse víctima de asedio moral en el trabajo. Los dos cuestionarios fueran aplicados electrónicamente e impresos entre mayo y septiembre de 2010. Los datos fueran tratados por estadística descriptiva. Los resultados mostraron que los sujetos se sintieron víctimas de asedio moral. Solamente las variables relacionadas a la caracterización del asedio moral presentaron asociación significativa. Entre las conductas más referidas, se destacaron: "Cuestionan las decisiones que usted toma" y "Usted recibe ataques verbales criticando trabajos realizados". Es importante la apertura de espacios de discusión sobre la violencia en el trabajo para que gestores puedan establecer medidas estratégicas de prevención y contención de este tipo de violencia a fin de garantizar la salud, la dignidad y el bienestar del profesional en el trabajo. También es importante discutir el tema en el ámbito académico, con el fin de dar mayor visibilidad a la cuestión, para que los futuras enfermeros puedan identificar y abordar adecuadamente este tipo de violencia. Trata-se de estudo descritivo-exploratório, de abordagem quantitativa, com o objetivo de identificar a percepção de enfermeiros sobre o assédio moral no trabalho, condutas vivenciadas e variáveis envolvidas. Na coleta de dados, utilizaram-se dois questionários: um socioprofissiográfico e outro para identificar as condutas de assédio moral, vivenciadas pelos sujeitos nos últimos 12 meses, o período e a frequência das condutas. Ao final do questionário, foi adicionada uma questão dicotômica que abordava a percepção do enfermeiro em relação a se sentir vítima de assédio moral no trabalho. Ambos os questionários foram aplicados no formato eletrônico e impresso, entre maio e setembro de 2010. Os dados foram tratados por estatística descritiva. Os resultados mostraram que parte dos sujeitos sentiu-se vítima de assédio moral. Somente as variáveis relacionadas à caracterização do assédio moral apresentaram associação significativa. Entre as condutas mais referidas, destacaram-se: "questionam as decisões que você toma" e "você recebe ataques verbais criticando trabalhos realizados". É importante a abertura de espaços para discussão sobre a violência no trabalho, para que gestores possam estabelecer medidas estratégicas de prevenção e contenção desse tipo de violência, a fim de garantir a saúde, a dignidade e o bem-estar no trabalho. Torna-se importante, também, discutir o assunto no espaço acadêmico, a fim de dar maior visibilidade ao tema, para que futuros enfermeiros possam identificar e enfrentar adequadamente esse tipo de violência.